Cooperative learning for intercultural classrooms case studies for inclusive pedagogy - Ferguson-Patrick, Kate; Jolliffe, Wendy (London Routledge, 2018)
"Cooperative Learning for Intercultural Classrooms helps both pre-service and in-service teachers to develop a well-researched pedagogy that supports inclusive practice for a globalised world. It provides: an overview of theoretical perspectives that illustrate why cooperative learning is an effective learning strategy; reviews research findings about how cooperative learning supports inclusion; and outlines the strategies and methods that support teachers in putting cooperative learning into practice."--Provided by publisher.
Introduction -- Understanding theory and principles -- Case studies of cooperative learning from around the world -- Implementing cooperative learning in the classroom -- Professional development approaches for cooperative learning -- Conclusion -- Appendix 1. Cooperative learning structures -- Appendix 2. Types of cooperative learning.
Includes bibliographical references and index.
Keywords: Group work in education -- Case studies; Motivation in education -- Case studies; Interaction analysis in education -- Case studies; Intercultural communication -- Study and teaching -- Case studies; Multicultural education -- Case studies